INTERAKSI SIMBOLIK DALAM KOMUNIKASI NONVERBAL PRIA METROSEKSUAL DI JAKARTA - Enifia Ramadhina Fibrayanti Putri (2021)
Metrosexual men is a person where they casually care so much about their looks, scents, grow with a big confidence, and happy to be the center of attention. Metrosexual men is someone that comes with different looks, that represent from symbolic interaction through nonverbal communication theory. This research talks about nonverbal communication in metrosexual men, linked with Interactionism Symbolic Theory from George Herbert Mead. The reason why this research should be done is to knowing how metrosexual men interpret nonverbal communication symbol by their looks with each metrosexual men. The author uses qualitative methods with symbolic interaction approach through interview and participant observation. The result that come from the research is metrosexual men with their nonverbal communication that they interpret by their looks seems positive and does not harm all parties.